ACTIO PAULIANA SEBAGAI UPAYA PERLINDUNGAN BAGI KREDITOR MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA DAN UNDANG-UNDANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) - Mantili, Rai (Departemen Hukum Perdata, 2020)
Actio Pauliana is the right given to a creditor to cancel the debtor’s agreement with a third party. The purpose of this actio pauliana is to avoid losses from its creditors, by requesting the court to cancel the debtor’s legal action which is deemed to be detrimental to his creditors. Actio Pauliana provisions apart from being regulated in the Civil Code, are also regulated in Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Repayment Obligation (UUKPKPU). However, the two rules have several diff erences. In this paper, the author wants to explain about Actio Pauliana which is regulated in the Civil Code and Actio Pauliana which is regulated in UUKPKPU in order to provide protection for creditors. This writing gives the result that Actio Pauliana’s lawsuit which is regulated in the Civil Code is submitted to the District Court and cannot be justifi ed and can take a long time. Unlike the case with Actio Pauliana which is regulated in the UUPKPU, the fi ling of a lawsuit is made to the Commercial Court and can be proven simply so that it can provide more protection for creditors.